Significance of ultrasonography of the terminal ileum in moderate Crohn's disease - Jović Jasna; Lukić-Kostić Leposava; Sekulović Slobodan (Vojnosanitetski Pregled)
Background/aim: Crohn's disease (CD) is a chronic granulomatous inflammatory disease of unknown etiology, involving any part of the gastrointestinal tract, and frequently followed by extra intestinal manifestations. The use of ultrasonography plays a significant role in diagnosing this disease, as well as in monitoring the effects of the therapy. The aim of this study was to assess the use of ultrasonographic diagnostics in the patients with moderate serious and the mild form of CD. Methods. The study involved 30 patients both sexes with CD of moderate form determined using the standard diagnostics, according to the Crohn's Disease Activity Index - CDAI ranging from 220−400. The patients were divided into two groups with CDAI > 320 (Ia), and CDAI between 220 and 320 (Ib), respectively. The Control group was made of 19 patients with the mildly active stage of the disease and the CDAI values in the range from 100−220. The patients were submitted to an ultrasonographic examination of the terminal ileum affected with CD in order to determine the length of the affected segment of intestine, the thickness of the wall, the changes of the structure of the wall, the changes of the surrounding mesenterium with the enlarged lymph nodes. CD complications, abscesses, and enteroenteral fistulas were investigated, too. Results. The comparison of the ultrasonographic findings of the three groups revealed that more serious clinical laboratory image of CD significantly correlated with the higher length of the affected segment (p < 0.001), higher thickness of the wall (p < 0.001), the higher number and the larger lymph nodes of the mesenterium (p < 0.001). Only the most serious patients were found to have abscess of the ileocecal area (Ia − 40%). There was no difference found between the groups regarding the occurrence of enteroenteral fistulas. Conclusion. Considering the obtained results and data from the literature, it could be concluded that an ultrasonographic examination of the ileocecal area plays an important role in the diagnostic procedure in the management of a patient with CD. Of particular significance is the possibility to use this examination in monitoring the effects of the therapy in patients with CD.